A remotely delivered exercise-based rehabilitation program for patients with persistent chemotherapy-induced peripheral neuropathy (EX-CIPN): Protocol for a phase I feasibility trial - Eric M. Antonen; Michelle B. Nadler; David M. Langelier; Kristin L. Campbell; David Flamer; Jang Hyuk Cho; Scott Capozza; Lisa Avery; Kelcey A. Bland; Scott Leatherdale; Jackie Manthorne; Jennifer M. Jones (PLoS ONE, 2025)
Background Chemotherapy-induced peripheral neurotoxicity (CIPN) is a prevalent adverse effect of chemotherapy agents that is estimated to be present in 2/3 of patients who receive neurotoxic chemotherapy. In 30–40% of these patients, CIPN signs and symptoms can persist for months or years post-treatment. Recent studies have supported exercise as a feasible and possibly effective intervention for CIPN; however, more rigorous studies are needed to confirm feasibility, estimate efficacy, and clarify risk. In response, we developed an innovative virtual exercise-based rehabilitation program (EX-CIPN) for cancer survivors with persistent CIPN. Methods This study is a phase I study conducted at the Princess Margaret Cancer Centre in cancer survivors with persistent CIPN, with a focus on feasibility, acceptability, and safety. A total of 40 patients aged 18 or older, with persistent CIPN at least 6 months after chemotherapy completion will be recruited and receive the EX-CIPN program. The EX-CIPN program is a 10-week virtual home-based intervention that includes an individualized exercise program supported with a mobile application (Physitrack), wearable technology (FitBit), and weekly virtual check-ins with an oncology exercise specialist. The primary outcome of feasibility will be assessed by examining accrual, retention, and adherence rates. Acceptability will be assessed through qualitative interviews. Safety events will be monitored and reported based on CTCAE v5. Secondary outcomes will be collected using questionnaires and physiological assessments at baseline (T1), after the intervention (T2), and 3-months after intervention (T3). Conclusion This phase I study will determine intervention feasibility, acceptability, and safety and will inform the planning for a future Phase II RCT with the EX-CIPN intervention.